Narrative Approaches in Play with Children. - Cattanach, Ann (Jessica Kingsley Publishers, 2007)
Narrative play is a way of communicating with children using imaginative stories and narratives to share and make sense of life events. This book describes using narrative play therapeutically with children who have lived in multiple families, children who have problems with social understanding and children who have learning difficulties. Ann Cattanach explains how children's stories and narratives, whether they are about real or imagined events, can be interpreted as indicators of their experiences, their ideas, and a dimension of who they are. She demonstrates this with examples of children.